DIFFERENCES OF SHORT-TERM CONSUMPTION OF SEMENDO ROBUSTA AND ARABICA COFFEE TOWARDS SWEET TASTE SENSITIVITY - Pudi Handayani; Irfannuddin Irfannuddin; Alifia Salsabila; Shanty Chairani; Nursiah Nasution (Fakultas Kedokteran Universitas Sriwijaya, 2023)
The most consumed and cultivated coffee in Indonesia is robusta and arabica coffee. Robusta and arabica coffee have different characteristics such as morphology, contents, and taste. Coffee consumption could cause alteration in taste sensitivity, especially sweet taste. Those could affect daily sugar consumption. The present study aimed to determine the differences of short-term consumption of semendo robusta and arabica coffee towards sweet taste sensitivity. This study used experimental study with a cross-over design approach that involved 21 students from the Faculty of Medicine Sriwijaya University. Semendo robusta and arabica coffee are used in this study. Sweet taste sensitivity was tested using the whole mouth test method by rinsed with sucrose solution at a concentration of 0,16, 0,32, 0,64, and 1,28 mol/l, which was given from the lowest concentration. Sweet taste sensitivity scores were rated at baseline and after the consumption of semendo robusta and arabica coffee which took place on different days. The lowest sucrose concentration that was correctly interpreted by the subject was noted as a taste sensitivity score. Data were analyzed using the Chi-square test. The chi-square test showed that the decrease in sweet taste sensitivity was more frequently happening after semendo arabica coffee consumption than semendo robusta coffee consumption (p<0,05). Short-term consumption of semendo arabica coffee has significantly increased the risk of sweet taste sensitivity reduction 4 times greater than semendo robusta coffee. There were differences in sweet taste sensitivity between short-term consumption of semendo robusta and arabica coffee.